Resposta de genótipos de cana-de-açucar à inoculação de bactérias diazotróficas no Rio Grande do Sul - Leal, Lineu Trindade (2011)
In southern Brazil is unknown the effect of diazotrophs inoculation in sugarcane (Saccharum officinarum). The evaluation of this practice and the selection of genotypes with high potential for biological N fixation (BNF) are essential for obtaining high yields of sugarcane in Rio Grande do Sul (RS). This study investigated the effect of diazotrophic bacteria inoculation and nitrogen fertilization on growth and productivity of sugarcane genotypes in RS. Two experiments were carried out in field conditions. In the experiment I, conducted in São Francisco de Assis/RS, the RB835089 genotype was grown on a Quartzipsament soil with and no-inoculation under two nitrogen levels (0 and 120 kg N ha-1). In the second experiment, conducted in Jaguari/RS on a Hapludalf, 10 genotypes were evaluated (RB835054, RB855156, RB925211, RB925345, RB986419, RB867515, RB975038, RB945177, RB947625 and RB987935) in three managements: nitrogen fertilization (120 kg N ha-1), without N and diazotrophic bacteria inoculation and control (without N and no-inoculation). In both experiments the diazotrophic bacteria inoculation in stems of genotypes was conducted with Embrapa-Agrobiology inoculant, composed of five diazotrophic strains. The evaluated parameters were: biometric variables, dry matter and total nitrogen accumulation and stems productivity. In the first experiment, inoculation increased growth and N accumulation. The stems productivity of the RB835089 inoculated was similar to the treatment that received nitrogen and was 50% higher than the control. In experiment II, sugarcane productivity ranged from 57 to 118 Mg ha-1. Four genotypes did not respond to fertilization and inoculation. Tillering was the variable most responsive to diazotrophic bacteria inoculation with a direct influence on the stems productivity. The response to inoculation varied among genotypes and was observed in genotypes RB855156, RB945177 and RB947625. These genotypes showed stems productivity that exceeded those of the control treatment, respectively, in 13 (18%), 21 (36%) and 13 (22%) Mg ha-1. The results of this study indicate that diazotrophic bacteria inoculation increases the stems productivity of the cane plant in responsive genotypes to practice, saving of nitrogen fertilizer through BNF.